2004
DOI: 10.1128/iai.72.8.4731-4740.2004
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of theAspergillus fumigatusGene Encoding Nucleolar Protein CgrA Impairs Thermotolerant Growth and Reduces Virulence

Abstract: Aspergillus fumigatusCgrA is the ortholog of a yeast nucleolar protein that functions in ribosome synthesis. To determine how CgrA contributes to the virulence of A. fumigatus, a ⌬cgrA mutant was constructed by targeted gene disruption, and the mutant was reconstituted to wild type by homologous introduction of a functional cgrA gene. The ⌬cgrA mutant had the same growth rate as the wild type at room temperature. However, when the cultures were incubated at 37°C, a condition that increased the growth rate of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
90
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 130 publications
(96 citation statements)
references
References 70 publications
(68 reference statements)
5
90
0
1
Order By: Relevance
“…Larvae of G. mellonella have been used previously to distinguish between Aspergillus species producing different levels of the immunosuppressive agent gliotoxin [7] and insects have also been used to quantify the role of rel A gene in contributing to the virulence of P. aeruginosa [16] and the virulence of mutants of A. fumigatus lacking the nucleolar protein Cgr A [11]. There is increasing attention being focused on the use of insects for measuring changes in microbial virulence -a process which has time and cost benefits to the researcher as well as ethical benefits in reducing the need to use mammals for this form of testing [3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Larvae of G. mellonella have been used previously to distinguish between Aspergillus species producing different levels of the immunosuppressive agent gliotoxin [7] and insects have also been used to quantify the role of rel A gene in contributing to the virulence of P. aeruginosa [16] and the virulence of mutants of A. fumigatus lacking the nucleolar protein Cgr A [11]. There is increasing attention being focused on the use of insects for measuring changes in microbial virulence -a process which has time and cost benefits to the researcher as well as ethical benefits in reducing the need to use mammals for this form of testing [3].…”
Section: Discussionmentioning
confidence: 99%
“…G. mellonella have also been utilised as a model for studying the virulence of Cryptococcus neoformans [10]. Bhabhra et al [11] have used an insect model to assess the virulence of mutants of A. fumigatus lacking the nucleolar protein Cgr A. In addition larvae of silkworms have been utilised to measure the efficacy of antibiotics in killing bacteria and a positive correlation with the results obtained from murine studies has been demonstrated [12].…”
Section: Introductionmentioning
confidence: 99%
“…Both inserts were gel-purified and 10 μg of each was used to transform wt-ΔakuA 36 protoplasts as previously described. 37 Loss of the derA gene was confirmed by Southern blot analysis of genomic DNA isolated from hygromycin resistant monoconidial isolates. Probe 1 (Fig.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 95%
“…First, an Aspergillus fumigatus mutant strain lacking CgrA, a key thermotolerance regulator, was hypovirulent in mice but fully virulent in Toll-deficient Drosophila. 47 Therefore, because flies are infected and maintained at 29°C, certain aspects of fungal virulence in mammals may not be accurately modeled in this organism; Galleria, which can be maintained at 37°C, the mammalian physiologic temperature, may be used instead, taking into account however that increasing the temperature of Galleria to 37°C itself alters cellular and humoral immune responses. 48,49 Second, the alb1-deficient Aspergillus fumigatus mutant, which is hypovirulent in mice and flies, 11,50 was hypervirulent in Galleria, in which it appears to trigger dysregulated immunopathology.…”
Section: Fungal Virulence Studiesmentioning
confidence: 99%